Pengaruh Pertumbuhan Perusahaan, Leverage, dan Profitabilitas Terhadap Kebijakan Dividen: Studi pada Perusahaan Food and Beverage di Bursa Efek Indonesia (BEI) Tahun 2021-2024 - Angel Mei Linda; Dwi Irawati; Agus Saur Utomo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The capital market plays a crucial role in supporting economic growth, particularly through investment activities carried out by both individual and institutional investors. Decisions regarding investment policies are influenced by several factors, including company growth, leverage level, and profitability. This paper focus on to examine the effect of company growth, leverage, and profitability on dividend policies among food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Dividend policy is considered an essential aspect of corporate financial management, as it not only reflects the management’s strategy in distributing net income but also indicates the company’s performance and future prospects. This research employs a quantitative approach. The data were collected from the financial statements of food and beverage companies for the 2021–2024 period, which were obtained from the official websites of the respective companies and the official IDX website. The findings reveal that company growth has a negative but insignificant effect on dividend policy, leverage has a positive and significant effect, while profitability shows a negative and insignificant influence on dividend policy.